(untitled) (Nigerian Journal of Technology, 2020)
The Liji area lithologically consists of inliers of granite and pegmatite members of the Pan-African granitoids surrounded by Cretaceous sedimentary deposits of Bima, Yolde, Pindiga and Gombe Formations. Epigenetic fracture-filling baryte mineralization hosted by granite, pegmatite and Bima Sandstone were delineated, sampled and analyzed for rare-earth elements (REEs) and stable sulphur isotope geochemistry. The REEs of the distal (unaltered) rocks indicated normal values (26.15-36.81 ppm) before mineralization was marked by enrichment of light rare-earth elements (LREEs) (27.94 ppm) relative to the heavy rare-earth elements (HREEs) (5.34 ppm) and negative Eu anomalies typical of calc-alkaline granites of Pan-African age. The baryte separates were marked by enriched LREEs and depleted HREEs with pronounced positive Eu anomalies indicating the invasion and consequent deposition of baryte-rich hydrothermal fluid under oxidizing conditions in the N-S and E-W striking fractures. Stable sulphur isotope of the baryte gives values that ranged from 18.3 - 19.8o/oo CDT indicating that the source of sulphur is from ocean water and not from magmatic, fresh water and connate water sources from the nearby granite, pegmatite and sandstone. http://dx.doi.org/10.4314/njt.v39i3.6